Chronic administration of methamphetamine promotes atherosclerosis formation in ApoE−/− knockout mice fed normal diet. Issue 1 (November 2015) - Gao, Bo; Li, Lun; Zhu, Pengfei; Zhang, Mingjing; Hou, Lingbo; Sun, Yufei; Liu, Xiaoyan; Peng, Xiaohong; Gu, Ye
Abstract: Objective: Chronic methamphetamine (METH) abuse could induce neurotoxicity due to reactive oxygen species generation and sympathetic activation. Both factors are associated with atherosclerosis, so we tested the hypothesis that chronic METH administration might also promote atherosclerosis formation in Apo E−/− knockout mice fed normal diet. Methods and Results: Male ApoE−/− mice (6 weeks-old) were treated with saline (NS) or METH [4 mg/kg/day (M4) or 8 mg/kg/day (M8) through intraperitoneal injection] for 24 weeks. Atherosclerotic lesion area on oil red O stained en face aorta was dose-dependently increased in M4 and M8 groups compared to NS group. Percentage of atherosclerotic lesion area was significantly higher in M8 group compared to NS and M4 groups. Plasma CRP was increased and inflammatory cytokine (ICAM-1, VCAM-1, TNF-α, and INF-γ) expression on aortic root was upregulated in METH groups compared to NS group. Neuropeptide Y (NPY) protein and mRNA expressions in aortic root and myocardial tissue were determined by Western blot and real time PCR, which were significantly upregulated in M4 and M8 groups. Moreover, mRNA expressions of NPY1R, NPY2R and NPY5R in aortic and myocardial tissue were also significantly upregulated in M4 and M8 groups. Raw264.7 cells were treated with NPY, NPY receptor antagonists, METH (10 μM or 100 μM) with or without lipopolysaccharide (LPS), and the expressions of TNF-α, CRP, MCP-1 and reactive oxygen species (ROS) production were significantly increased in METH and LPS + METH groups compared to control and LPS groups. Co-treatment with NPY1R antagonist decreased the expressions of TNF-α, CRP and MCP-1 in NPY and METH treated cells. Conclusions: Chronic METH administration can promote inflammation and atherosclerotic plague formation in ApoE−/− mice fed normal chow. NPY might be involved in the pathogenesis of METH-induced atherogenic effects through NPY Y1 receptor pathway. Highlights: METH promotes atherosclerosis formation in APOE−/− mice. METH increases plasma, aortic and myocardial NPY expression in APOE−/− mice. METH increases inflammation expression and ROS production of macrophages in vitro.